Post hoc analysis of a randomised controlled trial: effect of vitamin D supplementation on circulating levels of desmosine in COPD. Issue 4 (5th October 2020) - Janssen, Rob; Serré, Jef; Piscaer, Ianthe; Zaal, Ruben; van Daal, Henny; Mathyssen, Carolien; Zanen, Pieter; van den Ouweland, Jody M.W.; Janssens, Wim
Background: Vitamin D supplementation lowers exacerbation frequency in severe vitamin D-deficient patients with COPD. Data regarding the effect of vitamin D on elastin degradation are lacking. Based on the vitamin's anti-inflammatory properties, we hypothesised that vitamin D supplementation reduces elastin degradation, particularly in vitamin D-deficient COPD patients. We assessed the effect of vitamin D status and supplementation on elastin degradation by measuring plasma desmosine, a biomarker of elastin degradation. Methods: Desmosine was measured every 4 months in plasma of 142 vitamin D-naïve COPD patients from the Leuven vitamin D intervention trial (100 000 IU vitamin D3 supplementation every 4 weeks for 1 year). Results: No significant association was found between baseline 25-hydroxyvitamin D (25(OH)D) and desmosine levels. No significant difference in desmosine change over time was found between the placebo and intervention group during the course of the trial. In the intervention arm, an unexpected inverse association was found between desmosine change and baseline 25(OH)D levels (p=0.005). Conclusions: Vitamin D supplementation did not have a significant overall effect on elastin degradation compared to placebo. Contrary to our hypothesis, the intervention decelerated elastin degradation in vitamin D-sufficient COPD patients and not in vitamin D-deficient subjects. Vitamin D supplementation does not have a significant overall effect on elastin degradation. Vitamin D decelerates elastin degradation in vitamin D-sufficient, but not in vitamin D-deficient, COPD patients. https://bit.ly/2A9H9P7